Testing, training, and optimising performance of track cyclists: a systematic mapping review - Stadnyk, A. M. J.; Impellizzeri, F. M.; Stanley, J.; Menaspa, P.; Slattery, K. M. (Sports Medicine, 2022)
Background: Track cyclists must develop mental, physical, tactical and technical capabilities to achieve success at an elite level. Given the importance of these components in determining performance, it is of interest to understand the volume of evidence to support implementation in practice by coaches, practitioners, and athletes. Objective: The aim of this study was to conduct a systematic mapping review to describe the current scale and density of research for testing, training and optimising performance in track cycling. Methods: All publications involving track cyclist participants were reviewed from four databases (PubMed, SPORTDiscus, Academic Search Complete, Cochrane Library) plus additional sources. Search results returned 4019 records, of which 71 met the inclusion criteria for the review. Results: The review revealed most published track cycling research investigated athlete testing followed by performance optimisation, with training being the least addressed domain. Research on the physical components of track cycling has been published far more frequently than for tactical or technical components, and only one study was published on the mental components of track cycling. No true experimental research using track cyclists has been published, with 51 non-experimental and 20 quasi-experimental study designs. Conclusions: Research in track cycling has been growing steadily. However, it is evident there is a clear preference toward understanding the physical—rather than mental, tactical, or technical—demands of track cycling. Future research should investigate how this aligns with coach, practitioner, and athlete needs for achieving track cycling success.